2022
DOI: 10.1111/iju.14788
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Comment to Expanding the limits of nephron‐sparing surgery: Surgical technique and mid‐term outcomes of purely off‐clamp robotic partial nephrectomy for totally endophytic renal tumors

Abstract: On-clamp versus off-clamp partial nephrectomy: propensity score-matched comparison of long-term functional outcomes. Int. J. Urol. 2019; 26: 985-91. 24 Zhang Y, Ouyang W, Wu B et al. Robot-assisted partial nephrectomy with a standard laparoscopic ultrasound probe in treating endophytic renal tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Renal cell carcinoma (RCC) is the 6th most frequently diagnosed cancer in men and the 10th in women, representing the 3rd most frequent genitourinary malignancy worldwide and the 13th most common cause of cancer death worldwide [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…Renal cell carcinoma (RCC) is the 6th most frequently diagnosed cancer in men and the 10th in women, representing the 3rd most frequent genitourinary malignancy worldwide and the 13th most common cause of cancer death worldwide [ 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ].…”
Section: Resultsmentioning
confidence: 99%
“…With the spread of this concept and improvements in surgical technology, the application of PN for renal tumors has been extended to more challenging cases, including ERTs ( 1 ). Although several authors have reported their successful experiences and beneficial results ( 19 21 ), the evidence in support of PN as a standard is weak. Due to the highly complex branching anatomical structure, it is challenging to remove deep endophytic tumors and suture incised renal parenchyma and hilar structures without increasing perioperative complications; this requires considerable anatomical knowledge and technical skill ( 2 , 9 ).…”
Section: Discussionmentioning
confidence: 99%